Sewer subsidies from overflows and pipe leaks dominate urban stream solute loads in all storm events - Forgrave, Rebecca K.; Elliott, Emily M.; Bain, Daniel J. (Frontiers in Environmental Science, 2023)
Stream channel burial drastically alters watershed flowpaths by routing surface waters underground and increasing the potential for interactions between stream water and urban infrastructure such as storm and sanitary sewers. While numerous studies have investigated storm event solute loads from urban watersheds, the influences of stream channel burial and sewer overflows are often overlooked. This study uses grab samples and natural abundance stable isotope tracers to quantify the event dynamics of solute concentration-discharge relationships as well as cumulative loads in a buried urban stream. Our results demonstrate that different solutes, as well as different sources of the same solute (atmospheric NO3- and sewer-derived NO3- differentiated by the Δ17O tracer), are delivered via separate watershed flowpaths and thus have different timings within the event and contrasting relationships to flow. This inter-event variability reveals dynamics that result from temporal and spatial heterogeneity in infiltration, exfiltration, and pipe overflows. These results can help guide system-wide infrastructure maintenance as cities seek to meet challenges in sustaining and improving water quality as infrastructural systems age.